Microarray technology through applications [ - Falciani, Francesco (New York ; London : Taylor & Francis Group, 2007)
Provides an understanding, from an applications perspective, of the diverse range of concepts required to master the experimental and data analysis aspects of microarray technology.
1. Introduction to microarray technology -- 2. Immunoprecipitation with microarrays to determine the genome-wide binding profile of a DNA-associated protein -- 3. Use of single nucleotide polymorphism arrays : design, tools, and applications -- 4. In vitro analysis of gene expression -- 5. The analysis of cellular transcriptional response at the genome level : two case studies with relevance to bacterial pathogenesis -- 6. Functional annotation of microarray experiments -- 7. Microarray technology in agricultural research -- 8. Protein microarrays -- 9. Experimental protocols -- 10. Manufacturing arrays -- 11. Expression profiling -- 12. Other applications
Description based on print version record
Includes bibliographical references and index
Keywords: DNA microarrays; Gene Expression Profiling; Oligonucleotide Array Sequence Analysis -- methods; Genomics -- Methods; Research Design